Study Planning of Check Dam Using Waste Tires at Sumbersari UB Forest Area - Runi Asmaranto; Melvin Al Ishar; Anggara Wiyono Wit Saputra (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2024)
A check dam is a construction solution to overcome various catchment area challenges, especially erosion and sedimentation control in the upstream region. The strategic implementation of this plan includes various methodologies such as topographic, geotechnical identification, hydrological analysis, sedimentation analysis, material specification, hydraulic analysis, stability analysis, storage capacity analysis, and budget plan development. The purpose of this research is to check dam planning using waste tires which includes sediment discharge, detailed dimensions of the building, and building safety, to the required cost budget plan by reviewing the aspects of environmentally friendly, low cost, and waste utilization by sustainable development goals. The type of sediment flow that occurs is debris flow with a sediment discharge rate of 25,939 m3/s, due to the flood discharge phenomenon with a significant 25-year return period is 10,580 m3/s. The safety number of the proposed check dam design using the calculation of forces acting and Plaxis 2D V20 software has exceeded the safety permit requirements with various conditions that may occur at the study site. In a single flood, this check dam can effectively mitigate for approximately 4 days. To implement this development plan, an estimated budget of IDR773.472.940 has been projected.